Aqueous-Medium Arsenic(V) Removal Using Iron Oxide-Coated Ignimbrite - Velarde Apaza, Lelie Diana (2024)
Arsenate As(V) is a toxic contaminant commonly found in aquifers and groundwater that poses significant risks to human health. The effective treatment of arseniccontaminated water is therefore crucial for safeguarding public health. This study investigates removing As(V) using iron oxide-coated ignimbrite in batch experiments by varying the adsorbent dosage, initial As(V) concentration, contact time, and system temperature. The adsorption experiments revealed that the Langmuir isotherm model better fit the data (R2 = 0.99) than the Freundlich model (R2 = 0.73). According to the Langmuir model, the maximum adsorption capacity of As(V) on the iron oxide-coated ignimbrite was 4.84 mg·g −1 ± 0.12 mg·g −1 of As(V), with a standard deviation of ±0.05 mg·g −1 after 2 h of exposure with 0.15 g/50 mL iron oxide-coated ignimbrite adsorbent concentration. In the kinetic analysis, the pseudo-first-order model best described the adsorption process at 283 K, 293 K, and 303 K, although the pseudo-second-order model also showed an adequate fit, particularly at 293 K. This indicates that, while the pseudo-first-order model is generally more suitable under these conditions, the pseudo-second-order model may also apply under certain circumstances. The results of the batch experiments demonstrate that iron oxide-coated ignimbrite is a promising adsorbent for effectively reducing high concentrations of As(V) in contaminated water